The role of ethylene in metabolic acclimations to low oxygen - Hartman, Sjon; Sasidharan, Rashmi; Voesenek, Laurentius A. C. J. (The New phytologist, 2021)
Submerged plants ultimately suffer from shortage in cellular oxygen availability (hypoxia) as a result of impaired gas diffusion underwater. The gaseous plant hormone ethylene is rapidly entrapped in submerged plant tissues and is an established regulator of morphological and anatomical flood-adaptive responses. Multiple recent discoveries suggest that ethylene also plays a crucial role in hypoxia anticipation and metabolic acclimation during plant submergence. Ethylene was shown to accelerate and enhance the hypoxic response through enhanced stability of specific transcription factors (group VII ethylene response factors). Moreover, we suggest that ethylene could play an important role in the induction of autophagy and promote reactive oxygen species amelioration, thereby contributing to enhanced survival during flooding, hypoxia, and reoxygenation stress.